Dampak Korea Wave Terhadap Prilaku Remaja Di Era Globalisasi - Lisa Anggraini Putri (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Along with the development of technology in this globalization era, it is very easy for humans to obtain information, one of which is by accessing the development of kpop world. The more easy it is to get this information, causing teenagers to become fanatical about what they are idolizing. As a result of the teenage fanatics causes several positive and negative impacts on him. The cause of the drama series, music, fashion, cosmetics, culture, social media. The increase in the development of this newspaper wave is very necessary to be discussed and must be considered by parents in seeing the development of their children. In this journal the author discusses the positive and negative effects of this kpop development. Data taken by the author is obtained from books, journals, internet, newspapers. To address this and reduce adolescent fanaticism towards kpop, the writer shares the ways that parents need to do.